2022
DOI: 10.1037/dev0001416
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial choices: How do young children evaluate considerate and inconsiderate behavior?

Abstract: Adults often act considerately toward others, for example, by leaving the last cookie on a plate or stepping aside on a busy sidewalk. What do young children infer from observing considerate behavior? In three preregistered studies, we assess how young children evaluate considerate and inconsiderate behavior by showing them animated videos in which targets make decisions that either leave or limit choice options for others. Study 1 (N = 372 6-to 12-year-old children, 170 girls, 187 boys [15 not reported], 84.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previous research has shown that children around ages 5-6 years, as well as adults, value socially mindful actions where one leaves a choice for others (Van Doesum et al, 2013;Sierksma et al, 2022;Zhao et al, 2021). However, the motivations underlying such actions can vary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has shown that children around ages 5-6 years, as well as adults, value socially mindful actions where one leaves a choice for others (Van Doesum et al, 2013;Sierksma et al, 2022;Zhao et al, 2021). However, the motivations underlying such actions can vary.…”
Section: Discussionmentioning
confidence: 99%
“…For each measure, participants were also asked to justify their judgments. These measures have been widely used in previous studies measuring young children's social evaluations of both direct and indirect prosocial actions (Heyman et al, 2016;Sierksma et al, 2022;Zang et al, 2023;Zhao et al, 2021;Zhao & Kushnir, 2023).…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if Cindy takes one of the two apples, leaving two different options (i.e., one apple and one pear), then the person waiting behind her will be able to choose their preferred type of fruit. Recent studies have termed such actions that leave a choice for others as “socially mindful actions,” and shown that adults and children by age 5−6 evaluate someone leaving a choice for others as “nicer” than someone leaving no choice for others (Van Doesum, Van Lange, & Van Lange, 2013; Van Lange & Van Doesum, 2015; Zhao et al., 2021; Sierksma, Klootwijk, & Lee, 2022).…”
Section: Introductionmentioning
confidence: 99%